Strategi Pemasaran Untuk Meningkatkan Daya Saing UMKM Molly’s Coffee - Rimadias, Santi; Alvinnu, Alexandria; Carita, Herlina Reva; Gita, Dea Sapta (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Micro, Small and Medium Enterprises (MSMEs) are currently experiencing a quite difficult situation in the midst of a changing business environment and increasingly fierce business competition on a national and international scale. MSMEs as one of the supporters of economic growth, especially in Indonesia, need more attention because the increase in the MSME sector and the reduction of poverty rates are indicators of development success for the country. This study seeks to design a marketing strategy for Molly's Coffee SMEs by using a qualitative approach, combining observations, in-depth interviews, and SWOT analysis. Primary data was obtained from owners and customers of Molly's Coffee SMEs. The results reveal substantial growth opportunities, particularly through the refinement of marketing strategies. These findings highlight the potential of SMEs to increase their competitiveness and support sustainable economic development by utilizing digital devices efficiently